Level of demand for stimulation in post-myocardial infarction patients - Koprianiuk, Agata; Olajossy, Marcin (Current Problems of Psychiatry, 2011)
The aim of the study was to assess level of demand for stimulation in patients after myocardial infarction in comparison to healthy people. Study group and methods: Research was conducted in a group of 60 people. Clinical group comprised 30 patients after first myocardial infarction and 30 healthy people 30 (control group). Clinical group included 60% of males and 40% of females. All the patients were assessed using sociodemographic questionnaire worked out by the authors and Zukerman’s Sensation Seeking Scale adapted by E. Oleszkiewicz-Zsurzs. Results and conclusions: Based on obtained results the following conclusions were made: 1. Stimulation demand level did not differ between the group of patients after myocardial infarction and the control group of healthy people.